Evolve! : - Kanter, Rosabeth Moss (Harvard Business School Press, 2001)
Contents: Alice in Tomorrowland: Will the Young Lead the Way? ; Waves of Raves: Strategy as Improvisational Theater; Connecting the Dots: Nurturing Networks of Partners; From Cells to Communities: Deconstructing and Reconstructing the Organization; On Track to Tomorrow: Getting Change Rolling